Posterity is now: practicing museum anthropology, collections care, and collaborative research with Indigenous peoples - Shannon, Jennifer A., author; University of Wyoming Press, publisher (Colorado State University. Libraries, 2025)
A handbook providing theoretical and pragmatic guidance for embracing collaborative research and collections care for scholars who want to do research with Tribal communities based on 20 years of teaching and practice in museums and anthropology.--Provided by publisher.
Introduction -- Part 1: Collaboration Is Theory in Motion -- Part 2: Museum Anthropology -- Part 3: Collections Access and Care -- Part 4: Collaborative Research -- Conclusion: Reimagining Anthropology and the Museum.
Keywords: Indigenous peoples -- Research; Museums and Indigenous peoples; Indians of North America -- Museums; Anthropological museums and collections; Museums and community; Ethnological museums and collections